1980
DOI: 10.1038/ki.1980.110
|View full text |Cite
|
Sign up to set email alerts
|

Role of vasopressin in the impaired water excretion of glucocorticoid deficiency

Abstract: The mechanism whereby glucocorticoid deficiency impairs renal water excretion was studied in the conscious mineralocorticoid-replaced, adrenalectomized rat. Control animals received physiologic replacement with prednisolone, and experimental animals were deprived of glucocorticoid hormone for either 1 or 14 days. The control animals excreted 95 +/- 1.9% of an acute water load (30 ml/kg) in 3 hours, a value significantly higher than the volume excreted by animals deprived fo glucocorticoid hormone for 1 day (70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
4

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(50 citation statements)
references
References 28 publications
1
45
0
4
Order By: Relevance
“…Glucocorticoids have been found to act directly on the hypothalamus and tonically inhibit ADH release by magnocellular neurosecretory neurons [22], and plasma ADH has been found to increase in glucocorticoid deficiency [23]. These findings suggest that sustained and nonsuppressive ADH secretion because of the glucocorticoid deficiency may have played a role in the pathogenesis of hyponatremia in the present case; however, that fails to fully explain the impaired water diuresis on the second admission.…”
Section: Discussionmentioning
confidence: 34%
“…Glucocorticoids have been found to act directly on the hypothalamus and tonically inhibit ADH release by magnocellular neurosecretory neurons [22], and plasma ADH has been found to increase in glucocorticoid deficiency [23]. These findings suggest that sustained and nonsuppressive ADH secretion because of the glucocorticoid deficiency may have played a role in the pathogenesis of hyponatremia in the present case; however, that fails to fully explain the impaired water diuresis on the second admission.…”
Section: Discussionmentioning
confidence: 34%
“…Pero el mecanismo es distinto al aceptado para la deficiencia de mineralocorticoides, desde el momento que por la deficiencia de glucocorticoides per se no se genera hipovolemia ni balance negativo de sodio. (8) Es conocido el rol de la vasopresina en la generación de hiponatremia euvolémica, debido a insuficiencia suprarrenal o hipotiroidismo (9,10,11,12,13) Parece claro sin embargo, que existen factores independientes de la vasopresina que también están comprometidos en la excreción alterada del agua que cursa con la deficiencia de glucocorticoides. Así, mientras el componente vasopresina-dependiente puede ser observado en ratas adrenalectomizadas privadas de glucocorticoides por 24 horas, el efecto vasopresina independiente de la excreción de agua ocurre luego de 2 semanas de deficiencia de glucocorticoides, en ratas deficientes en vasopresina.…”
Section: Discussionunclassified
“…In addition, the expression of aquaporin-2 (AQP-2) water channel mRNA and protein in kidney was upregulated in glucocorticoid-deficient rats (12). Hydrocortisone replacement corrected the defect in renal water excretion and normalized plasma AVP levels and kidney AQP-2 mRNA expression in glucocorticoid deficiency (6,7,12).…”
Section: Introductionmentioning
confidence: 96%
“…Studies performed in isolated glucocorticoid deficiency showed that impaired water excretion occurred in the patients with hypopituitarism and in experimental models of glucocorticoid deficiency (3,(5)(6)(7)(8)(9)(10). Non-suppressible release of arginine vasopressin (AVP) was found despite hypo-osmolality which should suppress AVP release to undetectable levels (3,6,7,11). In addition, the expression of aquaporin-2 (AQP-2) water channel mRNA and protein in kidney was upregulated in glucocorticoid-deficient rats (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation